The Assessment of Neutrophil-to-Lymphocyte Ratio in Obesity: A Descriptive Study on University Students in Surabaya, Indonesia - Damayanti, Inggit; Raharjo, Budiono; Setiawan, Heru; Herawaty, Wike; Linggawan, Stephani; Sumarpo, Anton; Bintoro, Siprianus Ugroseno Yudho (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT The incidence of obesity worldwide is rapidly increasing, both in developed and developing countries. Obesity, particularly central obesity, is an inflammatory condition occurring within the body. The neutrophil-to-lymphocyte ratio (NLR) is a simple biomarker used to indicate the inflammatory response. This study aims to determine the profile of the neutrophil-to-lymphocyte ratio in students with obesity at the Faculty of Medicine, Universitas Wijaya Kusuma Surabaya.  This study employs a descriptive-analytic method with a cross-sectional approach. The study population comprises students from the Faculty of Medicine, Universitas Wijaya Kusuma Surabaya; 47 individuals, with 30 obese individuals and 17 individuals with a normal BMI. The results showed that the average neutrophil-to-lymphocyte ratio (NLR) for individuals with a normal BMI is 1,95. In contrast, the average NLR for obese individuals is 2,09. There is an increase in the average neutrophil-to-lymphocyte ratio (NLR) among obese students at the Faculty of Medicine, Universitas Wijaya Kusuma Surabaya. Keywords: Obesity, Neutrophil, Lymphocyte, Neutrophil-To-Lymphocyte Ratio